Analysis on the Characteristics of Crustal Structure and Seismotectonic Environment in Zigui Basin, Three Gorges - Wu, Yunlong; Pei, Junling; Wang, Ze; Zhang, Yi; Yuan, Huaqing (Frontiers in Earth Science, 2021)
The Zigui Basin in the Three Gorges area is a syncline running in the north–south axial direction; the sediments in the basin are mainly late Triassic–late Jurassic sandy and argillaceous rocks. Since the Three Gorges Project began undergoing impoundment in May 2003, nearly 20,000 mini–earthquakes have occurred in the Zigui–Badong section, including five earthquakes with magnitudes above Ms 5.0. Herein, a 3D gravity inversion method was introduced to investigate the density structure of the Zigui Basin and its adjacent areas. Comprehensive analysis of the geological structure of the area was carried out, based on focal mechanism solutions of six moderate–strong earthquakes in the area. The Zigui Basin is a low–density area from the periphery, and the sediment thickness in the east is higher than that in the west and the density lower than that in the west. The shallow part of the Zigui Basin is a weak bottom layer prone to slippage, and the deep part (5–10 km) could comprise lithological strata such as limestone, sandstone, and shale, which easily undergo dissolution by leaking reservoir water. Under the external force of long–term infiltration and loading–unloading of the reservoir water, cracks in the deep strata expand and squeeze, leading to an earthquake. Furthermore, new buried faults in the west and southeast edges of the core of the Zigui Basin could also trigger an earthquake under long–term pressurization and reservoir water penetration.